Flexural and Shear Behavior of 3D Printed Reinforced Concrete Beams: An Experimental Study - Franky Budiman; Alvin Halim; Jimmy Chandra; Pamuda Pudjisuryadi (Civil Engineering Dimension, 2023)
3D Concrete Printing (3DCP) provides many advantages for construction industry especially on productivity, waste, labor, and environment. Many researches have been conducted on the material development for 3DCP. However, there are not many researches which study the structural behavior of 3DCP. This experimental research aims to analyze flexural and shear behavior of 3D printed reinforced concrete beams. Five longitudinal reinforcement ratios were used to analyze crack patterns, failure mode, ductility, and capacity of those beams. The experimental results were then compared with analytical results by using ACI design code. The results show that higher longitudinal reinforcement ratio yields higher flexural and shear capacity of 3DCP beams. Due to layer-by-layer printing process, 3DCP beams are prone to local failure of filaments. Placement of longitudinal reinforcement might initiate macroscopic voids which could cause slippage and sudden drop on the capacity. Furthermore, ACI code underestimates the capacity of 3DCP beams failing in shear by some margins.